2003
DOI: 10.1037/0022-0663.95.3.465
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive language approach to early literacy: The interrelationships among vocabulary, phonological sensitivity, and print knowledge among preschool-aged children.

Abstract: This article describes 2 points of view about the relationship between oral-language and literacy skills: The phonological sensitivity approach posits that vocabulary provides the basis for phonological sensitivity, which then is the key language ability supporting reading, and the comprehensive language approach (CLA) posits that varied language skills interact with literacy knowledge and continue to play a vital role in subsequent reading achievement. The study included 533 Head Start preschool-aged children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
299
1
24

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 425 publications
(347 citation statements)
references
References 91 publications
(166 reference statements)
23
299
1
24
Order By: Relevance
“…Interestingly, children's reaction times on the DCCS were positively correlated with their phonological awareness skills, indicating that children who had better phonological awareness skills took longer to respond on the DCCS task. Research has shown that children with higher phonological awareness are likely to have improved representations of language (Dickinson et al, 2003) and, as a consequence, may be better at representing complex rule structures (Blair & Razza, 2007). Since the DCCS task requires children to direct their attention resources to relational rules that determine how stimuli are to be sorted, it is entirely possible that children with better phonological awareness tried harder to overcome their attentional inertia (Honomichl & Chen, 2011), which resulted in longer processing times on the task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, children's reaction times on the DCCS were positively correlated with their phonological awareness skills, indicating that children who had better phonological awareness skills took longer to respond on the DCCS task. Research has shown that children with higher phonological awareness are likely to have improved representations of language (Dickinson et al, 2003) and, as a consequence, may be better at representing complex rule structures (Blair & Razza, 2007). Since the DCCS task requires children to direct their attention resources to relational rules that determine how stimuli are to be sorted, it is entirely possible that children with better phonological awareness tried harder to overcome their attentional inertia (Honomichl & Chen, 2011), which resulted in longer processing times on the task.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the manner in which the stimuli in the LSS task were presented (i.e., orally) and the type of stimuli (i.e., words commonly known by children), we speculated that the LSS would require children to quickly access their semantic knowledge base through the phonological loop in working memory. Thus, we assumed that children who had better phonological awareness skills would respond faster on the task, particularly since vocabulary and phonological awareness are related to one another (e.g., Dickinson, McCabe, Anastasopoulos, Peisner-Feinberg, & Poe, 2003). As a result, it was possible that children who were faster would also be more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…The most noteworthy oversight resulted in failure to acknowledge the contribution of early language to the emergence of phonological awareness. When the report was being written, a seminal description of emergent literacy conceptualized oral language as providing a platform for the development of phonological awareness (Whitehurst & Lonigan, 1998), a position that was echoed and extended by a subsequent review and data (Dickinson, McCabe, Anastasopoulos, Peisner-Feinberg, & Poe, 2003). Also, in the 1990s the hypothesis was advanced that the acquisition of increasing numbers of words with similar phonological and articulatory patterns results in a reorganization in how words are stored in the brain (Metsala, 1999;Metsala & Walley, 1998).…”
Section: Indirect Effects Of Early Language On Readingmentioning
confidence: 99%
“…Furthermore, there appear to be separable genetic influences on early precursors to these skills, with both behavioural and genetic linkages between preschool phonological processing measures and later word reading, and between preschool oral language abilities and later reading comprehension (4). Despite the possibility of unique genetic influences on these two foundations of literacy, they are not fully independent, as there is evidence of reciprocal interactions among oral language and phonological processing abilities and between word reading and reading comprehension skills (5).…”
Section: Etiological Factorsmentioning
confidence: 99%